Knocking out ARL13B completely abolishes primary ciliogenesis in cell lines - Divyanshu Mahajan; Hui Min Chia; Lei Lu (Scientific Reports)
Abstract Small G protein ARL13B localizes to the cilium and plays essential roles in cilium biogenesis, organization, trafficking, and signaling. Here, we established multiple ARL13B knockout cell lines using the CRISPR/Cas9 system. Surprisingly, all our cell lines lost their cilia completely, in contrast to the reported short cilium and reduced ciliogenesis phenotype. We found that multiple regions of ARL13B are necessary for a complete rescue. Additionally, we found that ARL13B knockout cells also lost their response to SMO-mediated hedgehog stimulation. Our work demonstrates the critical requirement of ARL13B for ciliogenesis and hedgehog signaling, at least in cultured cells, and suggests that ARL13B plays a more crucial role in ciliary function than previously understood.